Characterization and Validation of a Chronic Model of Cyclophosphamide-Induced Interstitial Cystitis/Bladder Pain Syndrome in Rats - Augé, Céline; Gamé, Xavier; Vergnolle, Nathalie; Lluel, Philippe; Chabot, Sophie (Frontiers in Pharmacology, 2020)
Interstitial cystitis / Bladder Pain Syndrome (IC/BPS) is a chronic inflammatory disease characterized by visceral pain and voiding symptoms. IC/BPS is still an unsolved enigma with ineffective diagnosis criteria and treatment. A main limitation in IC/BPS understanding is the lack of appropriate preclinical model. Cyclophosphamide (CYP) is commonly used as an experimental model for IC/BPS in rodent. However, the proposed models are very aggressive, contrasting with what occurs in clinic, and often associated with severe toxicity and high mortality rate. In addition, visceral pain, the hallmark symptom of IC/BPS, has been validated in only few of them. In this study, we developed a new chronic model of CYP-induced IC/BPS in female rat. In our protocol, no severe weight loss occurred and the survival rate was 100%. In accordance to human pathology, chronic CYP-injected rats developed severe painful behavior whereas only sparse inflammation was observed. Inflammatory response was characterized by bladder edema and focal urothelial damage but absence of massive infiltrate. Our chronic model showed persistent symptoms indicative for a central sensitization mechanism. We further demonstrate that CYP-induced chronic visceral pain was significantly reduced by curative treatment with clinically relevant compounds (gabapentin, ibuprofen and Ialuril®). We therefore developed and validated a rat model of chronic cystitis that shares strong similarity with human non-ulcerative IC/BPS features without overtly affecting the animal health. This model will thus provide mechanistic insights of the disease and help to evaluate therapeutic agents for IC/BPS.